ORAL READING CONTESTS OF LITERARY WORKS AS EXTRACURRICULAR ACTIVITIES IN LANGUAGE EDUCATION - Noto Kuniyuki (XALQARO ILMIY-AMALIY ANJUMAN “GLOBAL LINGVISTIKA: YANGI YONDASHUVLAR VA TADQIQOTLAR”, 2025)
This paper is a practical report on incorporating the reading aloud of literary works as an extracurricular activity in Japanese language learning. In the age of AI, this study revisits the significance and challenges of traditional learning activities by exploring the value of reading aloud—an approach that may be seen as classical. While there have been increasingly critical views toward oral reading of textbook passages in recent years, reading aloud as a creative activity differs in nature from simple oral reading. Furthermore, by organizing the reading aloud activity in the form of a contest, it proved to be a meaningful endeavor in terms of enhancing learners’ motivation, sense of achievement, and overall satisfaction with university life.